2017
DOI: 10.20937/rica.2017.33.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Organochlorine Pesticide Levels Between Human Blood Serum and Adipose Tissue

Abstract: The organochlorine pesticides, being lipophilic compounds, show extremely high thermodynamic stability and resistance to degradation processes in the environment and in living organisms. They accumulate in lipid rich tissues and distribute between transport compartment (blood) and store compartment (adipose tissue). The purpose of this study is to make a comparison between organochlorine pesticide levels in blood serum and adipose tissue and calculate the differences in their concentrations based on routine bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…It has been established that, in humans, the level of some dioxin-like PCBs, polychlorinated dioxins and furans in blood serum, when referred to the lipid fraction, sufficiently reflects its concentration in the adipose tissues of the human body [ 49 ]. Similar results have been reported for the ratio of the concentrations of some OCPs in human blood and adipose tissue samples [ 50 ]. It is known that DDT and its main metabolites described in this work are very close to PCBs and dioxins in terms of distribution coefficients and other physicochemical properties.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It has been established that, in humans, the level of some dioxin-like PCBs, polychlorinated dioxins and furans in blood serum, when referred to the lipid fraction, sufficiently reflects its concentration in the adipose tissues of the human body [ 49 ]. Similar results have been reported for the ratio of the concentrations of some OCPs in human blood and adipose tissue samples [ 50 ]. It is known that DDT and its main metabolites described in this work are very close to PCBs and dioxins in terms of distribution coefficients and other physicochemical properties.…”
Section: Resultssupporting
confidence: 89%
“…Here, it is necessary to make a small but fundamental reservation. Since in this study we did not directly measure the concentrations of PCBs in the adipose tissues of calves, then, despite the facts presented in the cited studies [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ], we formally have no right to assert that POPSH decreases their concentrations not only in the blood, but also in other tissues of the calves. This study will be accomplished in the near future, and for now, for our part, we will restrict ourselves to conclusions at the level of assumptions.…”
Section: Resultsmentioning
confidence: 84%
“…Martínez-Valenzuela et al (2017a) demonstrated that serum lipid OCPs concentrations represent an important indicator for both human biological matrices [102]. The authors measured higher pesticide concentrations in 126 pair samples of adipose tissue and blood serum during autopsies from Los Mochis Sinaloa, Mexico (higher concentrations correspond to b-HCH, pp'DDE and op'DDT in blood serum lipids; and pp'DDT shows higher concentrations in adipose tissue), with a significant linear association of lipid serum organochlorine pesticide concentrations with that in adipose tissue [102].…”
Section: Biomarkers Of Exposurementioning
confidence: 99%